Corrosion protection of carbon steel using a combination of Zr conversion coating and subsequent zinc-rich silicate coating with a flake ZnAl alloy - Nguyen Hoang; Truong Anh Khoa; Le Thi Nhung; Phan Minh Phuong; To Thi Xuan Hang; Nguyen Van Chi; Thanh-Danh Nguyen (Arabian Journal of Chemistry, 2022)
To improve the corrosion protection properties of zinc-rich silicate coatings on steel, zirconium pretreatment loaded with (3-aminopropyl)triethoxysilane (APTES) 0.025 % (v/v) and the partial replacement of spherical zinc by flake ZnAl alloy were investigated. DC polarization and electrochemical impedance spectroscopy (EIS) show that the zirconium pre-treated layer containing APTES improves the corrosion protection of the bare steel. Zinc-rich silicate coatings containing flake ZnAl with and without pretreatment were evaluated by EIS, salt spray test and pull-off test. Pretreatment with a zirconium conversion layer reduces corrosion products and adhesion loss (from 16.53% to 12.54%) while the performance of corrosion protection significantly increased from 2003 Ω.cm2 to 2640 Ω.cm2 in comparison with the non-pretreated samples. The results show that flake ZnAl pigment (5 wt%) significantly improves corrosion resistance and prolongs the duration of cathodic protection of zinc-rich silicate coatings.